Duloxetine and Subacute Pain after Knee Arthroplasty when Added to a Multimodal Analgesic Regimen: A Randomized, Placebo-controlled, Triple-blinded Trial. (September 2016) - YaDeau, Jacques T.; Brummett, Chad M.; Mayman, David J.; Lin, Yi; Goytizolo, Enrique A.; Padgett, Douglas E.; Alexiades, Michael M.; Kahn, Richard L.; Jules-Elysee, Kethy M.; Fields, Kara G.; Goon, Amanda K.; Gadulov, Yuliya; et al.
Abstract : Background: Duloxetine is effective for chronic musculoskeletal and neuropathic pain, but there are insufficient data to recommend the use of antidepressants for postoperative pain. The authors hypothesized that administration of duloxetine for 15 days would reduce pain with ambulation at 2 weeks after total knee arthroplasty. Methods: In this triple-blinded, randomized, placebo-controlled trial, patients received either duloxetine or placebo for 15 days, starting from the day of surgery. Patients also received a comprehensive multimodal analgesic regimen including neuraxial anesthesia, epidural analgesia, an adductor canal block, meloxicam, and oxycodone/acetaminophen as needed. The primary outcome was the pain score (0 to 10 numeric rating scale) with ambulation on postoperative day 14. Results: One hundred six patients were randomized and analyzed. On day 14, duloxetine had no effect on pain with ambulation; mean pain was 3.8 (SD, 2.3) for placebo versus 3.5 (SD, 2.1) for duloxetine (difference in means [95% CI], 0.4 [−0.5 to 1.2]; P = 0.386). Symptoms potentially attributable to duloxetine discontinuation at study drug completion (nausea, anxiety) occurred among nine patients (duloxetine) and five patients (placebo); this was not statistically significant ( P = 0.247). Statistically significant secondary outcomes included opioid consumption (difference in mean milligram oral morphine equivalents [95% CI], 8.7 [3.3 to 14.1], P = 0.002 by generalized estimating equation) over the postoperative period and nausea on day 1 ( P = 0.040). There was no difference in other side effects or in anxiety and depression scores. Conclusions: When included as a part of a multimodal analgesic regimen for knee arthroplasty, duloxetine does not reduce subacute pain with ambulation. Abstract : In a triple-blinded, randomized control trial of duloxetine, 60 mg/day for 14 days begun on the day of total knee arthroplasty versus placebo in 106 patients, duloxetine failed to reduce pain with ambulation on postoperative day 14, the primary outcome.